Energy Conservation for 3D Tropical Climate Model in Periodic Domains - Hui Zhang (Journal of Mathematics)
In this paper, we prove the energy conservation for the weak solutions of the 3D tropical climate model under some sufficient conditions. Our results are similar to Onsager’s conjecture which is on energy conservation for weak solutions of Euler equations.